The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1038/sj.cdd.4400671
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the potential proapoptotic molecule DD2 and increased synthesis of leukotriene B4 during allograft rejection in a marine sponge

Abstract: Sponges (Porifera) are a classical model to study the events during tissue transplantation. Applying the`insertion technique' autografts from the marine sponge Geodia cydonium fuse within 5 days. In contrast, allografts are rejected and destroyed. Here we show that during allograft rejection the cells in the grafts undergo apoptosis; 5 days after transplantation 46% of the cells show signs of apoptosis. In a previous study it was shown that during this process a tumor necrosis factor-like molecule is induced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 64 publications
2
17
0
Order By: Relevance
“…70 GCBHP2 expression is upregulated in sponge cells exposed to low Apical and initiator caspase homologs, pro-and antiapoptotic Bcl-2 family members. Caspase-dependent cell death observed in allograft rejection [67][68][69][70][71][72] (but not high) levels of tributyltin or heat shock, and GCBHP2 appears to have an antiapoptotic role. Mammalian cells transfected with GCBHP2 were somewhat resistant to serum starvation and tributylin-induced apoptosis.…”
Section: Out Of the Mainstream Into The Oceanmentioning
confidence: 99%
See 1 more Smart Citation
“…70 GCBHP2 expression is upregulated in sponge cells exposed to low Apical and initiator caspase homologs, pro-and antiapoptotic Bcl-2 family members. Caspase-dependent cell death observed in allograft rejection [67][68][69][70][71][72] (but not high) levels of tributyltin or heat shock, and GCBHP2 appears to have an antiapoptotic role. Mammalian cells transfected with GCBHP2 were somewhat resistant to serum starvation and tributylin-induced apoptosis.…”
Section: Out Of the Mainstream Into The Oceanmentioning
confidence: 99%
“…Although the autografts fuse within 5 days, approximately half of the cells in the allograft show positive TUNEL staining and characteristic DNA fragmentation during the same period. 67 Extracts made from allografts, but not autografts, cleave a caspase substrate, indicating caspase-like activity. 68 Apoptotic genes have been identified in several species of sponges, and two sponge caspases have been cloned (GEOCYCAS3l and GEOCYCAS3s).…”
Section: Out Of the Mainstream Into The Oceanmentioning
confidence: 99%
“…Until recent discoveries 1,2 it was assumed that the physiological cell death is restricted to multicellular organisms, which have separate germ and somatic cells. 3 Originally it was suggested to divide the physiological cell death into two processes: (a)`programmed cell death', describing the developmentally regulated elimination of specific cells during embryogenesis, 4 and (b)`apoptotis', describing morphological changes of dying cells.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies elucidated that in sponges, with the two demosponges Geodia cydonium and Suberites domuncula as the most thoroughly investigated examples, polypeptide sequences exist which comprise high sequence similarities to members of the wider Bcl-2 family 1,2 as well as to pro-apoptotic molecules containing the death domain. 2 Members of the Bcl-2 family are defined by the conservation of two domains, termed Bcl-2 homology domain-1 and -2 (BH1 and BH2). 12,13 The Bcl-2 family comprises pro-survival molecules, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical and immunohistochemical methods were later used to study apoptotic cell death in sponge extracts where caspase 3 activity was found to be greatly increased in allografts when compared with isografts (26,27). Higher expression of other molecules potentially related to apoptosis has been detected in allografts of several sponge species (28,29).…”
mentioning
confidence: 99%